400–450 MHz power amplifier with high‐order harmonic suppression for multi‐protocol transceiver. Issue 23 (1st November 2016) - Weng, Zhaoyang; Jiang, Hanjun; Dong, Jingjing; Li, Fule; Wang, Zhihua
Abstract : A combinational biasing technique is presented for a 400–450 MHz power amplifier (PA). By combining two class AB amplifiers with different conduction angles and optimising the design parameters as well, the 5th and 6th harmonics are greatly suppressed in the PA's output. The designed PA is fabricated in 65 nm CMOS technology. Measurement results show that with the presented technique the 5th and 6th harmonic suppressions can be improved by 13 and 17 dB, respectively, compared with a PA with a fixed conduction angle. The presented PA technique can find its important use in multi‐protocol transceivers.